2011
DOI: 10.4317/medoral.16.e317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chin position on natural head orientation reproducibility

Abstract: Background and aims: Establishment of natural head position (NHP) in radiography or photography by estimation, which is called natural head orientation (NHO), has been recently advocated by various studies. This study aimed to determine the effect of chin position on the accuracy and reproducibility of NHO in a more realistic way. Materials and Methods: NHP-based digital photographs of 33 adults with normal profile were modified using the computer software Supper-Goo and Photoshop technique to produce 99 profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…[26][27][28][29][30][31][32][33][34][35][36] Reorientation of radiographs according to standardized photographs made at the NHP is a reliable and objective method to standardize the radiographs at the NHP for cephalometric analysis. 42,43 NHP, a long proposed modification, yet not fully into practice, can be an 'ideal' reference for us to improve our cephalometric interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29][30][31][32][33][34][35][36] Reorientation of radiographs according to standardized photographs made at the NHP is a reliable and objective method to standardize the radiographs at the NHP for cephalometric analysis. 42,43 NHP, a long proposed modification, yet not fully into practice, can be an 'ideal' reference for us to improve our cephalometric interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…43 Various techniques have been used to establish and transfer head orientation to radiographs. To mention a few, Schmidth made use of a frame that encircled the skull, a plumb line and a protractor.…”
mentioning
confidence: 99%
“…38 Another study found that natural head orientation could be created with great reproducibility through orientation of profile images in different chin positions. 40 They found that although NHO may be influenced by Class II and Class III patients, this influence is not clinically significant. 40…”
Section: Relationship Of Natural Head Position To Craniofacial Morphomentioning
confidence: 95%
“…40 They found that although NHO may be influenced by Class II and Class III patients, this influence is not clinically significant. 40…”
Section: Relationship Of Natural Head Position To Craniofacial Morphomentioning
confidence: 95%
See 1 more Smart Citation